The Effect of the Digitalization System on Customer Service Performance in the Banking Business during Post-Pandemic - Paisal, Paisal; Afrizawati, Afrizawati; Fernando; Sabli, Habsah Binti Mohammad (Asean International Journal of Business, 2023)
This research was conducted to find out how the impact of the banking digitalization system on customer service performance in banking business activities. The data in this study used primary data collected by distributing questionnaires, interviews and observations to all Bank Negara Indonesia 46 customer service Palembang areas. The population used is the customer service of Bank Negara Indonesia 46 Palembang area, namely as many as 54 people and the sample taken from this study was taken using the saturated sampling method, namely as many as 54 people. Data analysis was carried out using the validity test, reliability test, simple linear regression test and hypothesis testing using the t test technique. Result show that the impact of digitalization has a positive influence on customer service performance , so that it can take over some of the roles and tasks of customer service) because the digital technology services offered have the features needed for customers to transact simple services in the banking sector without having to go through the customer.